Analisis Pengaruh Pembiayaan Mudharabah, Musyarakah, dan Murabahah Terhadap Profitabilitas Perbankan Syariah Yang Terdaftar Di Bank Indonesia (BI) Periode 2012-2016 - Khopipah Lubis (Asosiasi Dosen Akuntansi Indonesia, 2021)
The purpose of this research is to analyze the effect of mudharabah, musyarakah, and mudharabah finance on the profitability of Islamic Banks. The population in this research is all of Syariah Public Banks registered in Bank Indonesia (BI); those are 11 banks. But, in the population, there are two banks which do not have data on the variables of this research. There were 9 Syariah Public Bank which fulfill the requirement to be sample of the research. The sample was selected by using purposive sampling technique. In this research, the technique of data analysis used was multiple regression analysis with SPSS program.The result of this research shown that mudharabah, musyarakah and murabahah finances were not influence to the profitability of Islamic banks simultaneously, the significant value is 0,244. Partially, mudharabah was not affect to the profitability of the Islamic Bank with significant score 0,174, musyarakah also was not affect the profitability with significant score 0, 287. Furthermore murabahah was not affect the profitability with significant score 0, 424